Dual-mode ion-selective electrodes and distance-based microfluidic device for detection of multiple urinary electrolytes - Phoonsawat, Kamonchanok; Ozer, Tugba; Dungchai, Wijitar; Henry, Charles S. (ROYAL SOC CHEMISTRY, 2022)
Here, we developed a microfluidic paper device by combining ion-selective electrodes (ISE) and a distance-based paper device (dPAD) for simultaneous potentiometric and colorimetric detection of urine electrolytes including K+, Na+ and Cl-. The working and reference electrode zones were coated with polystyrene as a non-ionic polymer to improve hydrophobic properties on the paper surface for fabrication of K+-ISE and Na+-ISE. The layer of polymer coating was optimized to enhance the sensitivity of the ISEs. Under optimized conditions, the electrode surfaces were modified with carbon black to improve the electrochemical characteristics of the ISEs. The ISEs showed good performance with sensitivities of 54.14 +/- 3.94 mV per decade and 55.08 +/- 1.15 mV per decade for K+ and Na+ within the linear concentration range 0.100 mM-100 mM K+ and 5 mM-1 M Na+, respectively. The limits of detection (LOD) were 0.05 mM and 1.36 mM for K+ and Na+, respectively. The linear working range of Cl- was 0.50 to 50 mM and the LOD and limit of quantification (LOQ) were found to be 0.16 +/- 0.05 mM (3SD) and 0.53 +/- 0.05 mM (10SD), respectively. The dual-mode ISE-dPAD was validated in human urine and recoveries were obtained as 90-108%, 94-105%, and 90-96% for K+, Na+, and Cl-, respectively, showing successful application of the developed device in a complex matrix. The ISE-dPAD has advantages including low-cost ($ 0.33 per test), eco-friendly, portability, simple operation, the need of low sample volume (100 mu L), and simultaneous analysis on a single device.
Keywords: POTASSIUM INTAKE; SODIUM; CHLORIDE; HYPERTENSION; TIME; K+; Chemistry